“Uma formidável multidão” : autonomia Mbayá-Guaicuru na construção da fronteira no Alto Paraguai : os deslocamentos, a política indígena e as relações com os colonizadores na passagem do século XVIII para o XIX - Marinato, Francieli Aparecida (2023)
ABSTRACT: This thesis discusses the context of borderland disputes between Portuguese and Spanish Crowns in the Paraguay River Basin from the second half of the 18th century up to the early 19th century. Emphasis is given on the dynamics of the settlement, displacements, and negotiations promoted by the Mbayá-Guaicuru indigenous people. Despite the notorious records in historical sources of a great number of indigenous people in the composition of the borderland population, little was discussed about their performance in the geopolitical division of the central part of South America between the Luso-Hispanic countries. Part of the most recent historiography related to the subject, and, mainly, a document, produced by the military directly involved in this context, indicates the active presence of the indigenous people, with the Mbayá-Guaicuru people as protagonist. This study also focuses on the Mbayá-Guaicuru people politics and their relationship with the settlers, which was marked by frequent movements between indigenous villages and the military structures jammed amid the area disputed by the Iberian colonizers, as well as the Mbayá-Guaicuru alliances with other native peoples. By doing this, we identified the development of a Guaicuru indigineous policy which aimed to maintain autonomy and freedom, in order to insure their socioeconomic interests, native mobility, and territorial domain or at least of territorial niches in the resurgence of borderland conflicts. We also analyzed the Portuguese and Spanish disputes for the Guaicuru “friendship” and their alliance making with these indigenous populations considering the inverted optics of how natives established relations with colonial agents and how indigenous policies were conducted with the colonial powers at the borderland. Besides alternating treaties with the Iberian Crowns, the Guaicuru reinforced alliances and miscegenation with different native peoples, a fact that instigated us to understand the reasons and purposes of these relationships and such enhanced agency by this group. Our primary hypothesis is that the MbyáGuaicuru’s aim was to maintain autonomy – for which they had negotiated both economically and politically – and for transiting freely among the different colonial spaces, gaining the benefits and advantages, leading the relations with other indigenous groups, arranging and reinforcing the native autonomy, mainly their own. Therefore, we verify that the MbayáGuaicuru were inserted in the making process of the Luso-Hispanic frontier and had a significant performance, as they also competed to guarantee their territory and acted to preserve their autonomy and lifestyle.